Plasma sanguíneo desidratado na alimentação da Tilápia-do- Nilo - Araujo, Eric Portilho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study evaluated the inclusion of dehydrated blood plasma (PD) on Nile tilapia diet by a research divided in two stages: 1° Stage, after 60 days, was measured the productive performance and histological parameters of fish, whose received five diets: PD0 (control); PD 1,66; PD 3,32; PD 4,97; PD 6,63% of dehydrated blood plasma inclusion. 440 fish was randomized into 40 aquariums (250 L) with physic-biological filter and automatic system water control (26 ±1°C) on the 1°st. On the second stage, was evaluated hematological parameters of Nile tilapia juveniles, before and after the cold stress (16°C). During seven days, 60 fish were allocated in 30 aquariums (40 L), with individual aeration and filters, provided by a division in each, that assure individuals spaces. PD inclusion results presented greater weight gain, final weight and improves the intestinal integrity. Maintenance and/or stimulation of erythropoiesis was observed with the addition of PD, inferring better health and fish organic resistance exposed to stress by low temperature. Increased production of neutrophils and monocytes maintenance, demonstrated the stimulatory effect of PD on the innate immune system . The data was submitted to the analysis technique variance (P<0.05), complemented by the multiple comparison Tukey test. Regression analyzes were performed when the model was significant (R2>0.70). For outresults of the normal curve, was applied the nonparametric Kruskal-Wallis analysis (P<0,05), complemented by Mann-Whitney test comparisons. The inclusion of PD for Oreochromis niloticus on diet, improves growth performance, gut health, blood profile and organic resistance to stress by low temperature. Based on the results of growth performance and histology, is recommended the PD inclusion of 4.97 % on the diet, because it brings more benefits when compared to PD treatment without inclusion

Este estudo avaliou a inclusão de plasma sanguíneo desidratado (PD) na dieta da tilápia-do-Nilo por meio de uma pesquisa dividida em duas fases: na Fase I, com duração de 60 dias, avaliou-se o desempenho produtivo e parâmetros histológicos dos peixes alimentados com cinco dietas: PD0 (controle); PD 1,66; PD 3,32; PD 4,97; PD 6,63% de inclusão de PD. Para isto distribuiu-se 440 peixes em 40 aquários de 250 L dotados de filtro físico e biológico com controle de temperatura (26 ±1°C). Na Fase II avaliou-se os parâmetros hematológicos de juvenis de tilápia-do- Nilo, antes e após o estresse por baixa temperatura (16°C) durante sete dias, utilizandose de 60 peixes distribuídos aleatoriamente em 30 aquários de 40 L, dotados de biofiltros e aeração individuais. A inclusão de PD determinou maior ganho de peso e peso final e melhora da integridade intestinal. Manutenção e/ou estímulo à eritropoiese foi observado com a inclusão de PD inferindo melhor higidez e resistência orgânica aos peixes expostos ao estresse por baixa temperatura. Aumento na produção de neutrófilos e manutenção de monócitos demonstrou o efeito estimulatório do PD sobre o sistema imune inato. Os dados foram submetidos à análise de variância (P<0,05), complementado pelo teste de comparações múltiplas de Tukey. Foram realizadas análises de regressão nos casos em que o modelo foi significativo (R2 >0,70). Para dados fora da curva de normalidade, aplicou-se o teste não paramétrico de Kruskal- Wallis (P<0,05), complementados com o teste de comparações de Mann-Whitney. A inclusão de PD à dieta de Oreochromis niloticus melhora o desempenho produtivo, a saúde intestinal, perfil hematológico e resistência orgânica ao estresse por baixa temperatura. Com base nos resultados de desempenho e histologia, recomenda-se o nível de inclusão de 4,97% à dieta, pois traz mais benefícios quando comparado ao ...
Dehydrated blood plasma in the feeding nile tilapia
Keywords: Peixe - Alimentação e rações; Hematologia; Tilapia (Peixe); Plasma sanguíneo; Tilapia